2019
DOI: 10.1002/ijc.32191
|View full text |Cite
|
Sign up to set email alerts
|

EGFR‐targeted therapy alters the tumor microenvironment in EGFR‐driven lung tumors: Implications for combination therapies

Abstract: Immune checkpoint inhibitors targeting the programmed cell death receptor/ligand 1 (PD‐1/PD‐L1) pathway have profoundly improved the clinical management of non‐small‐cell lung cancer (NSCLC). Nevertheless, the superiority of single‐agent PD‐1/PD‐L1 inhibitors in pretreated EGFR mutant patients has turned out to be moderate. One proposed mechanism for poor response to immune checkpoint inhibitors is an immunosuppressive tumor microenvironment. Therefore, we utilized two autochthonous EGFR‐driven lung tumor mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 49 publications
2
123
0
Order By: Relevance
“…Furthermore, preclinical results have shown that EGFR activation can upregulate intrinsic PD-L1 expression on tumor cells, which induces T cell apoptosis and contributes to the immune escape of EGFR-mutant NSCLC. In addition, EGFR-TKIs can potentiate the induction of MHC class I and II molecules in response to IFN-γ and enhance T cell-mediated tumor killing [47]. In this regard, these studies provide a theoretical basis to support the potential synergistic effects of combining PD-1/PD-L1 inhibitors and EGFR-targeted therapy in NSCLC patients carrying EGFR mutations accompanied by upregulation of PD-L1 expression.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Furthermore, preclinical results have shown that EGFR activation can upregulate intrinsic PD-L1 expression on tumor cells, which induces T cell apoptosis and contributes to the immune escape of EGFR-mutant NSCLC. In addition, EGFR-TKIs can potentiate the induction of MHC class I and II molecules in response to IFN-γ and enhance T cell-mediated tumor killing [47]. In this regard, these studies provide a theoretical basis to support the potential synergistic effects of combining PD-1/PD-L1 inhibitors and EGFR-targeted therapy in NSCLC patients carrying EGFR mutations accompanied by upregulation of PD-L1 expression.…”
Section: Introductionmentioning
confidence: 87%
“…Changes in expression of membranous immunomodulatory molecules in the TME and release of immunosuppressive soluble factors, such as TGF-β, IL-10 and adenosine (ADO) [47,48], play a crucial role in tumor progression.…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR-targeted therapy such as EGFR tyrosine kinase inhibitors (EGFR-TKIs) alters the tumor microenvironment in lung cancer (Matsumoto et al, 2019). EGFR-TKIs could increase cytotoxic CD8 + T cells and dendritic cells in the tumor environment of lung cancer (Jia et al, 2019). FGL2 also increase cytotoxic CD8 + T cells and dendritic cells in the tumor environment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%